PERAN ADMINISTRASI KURIKULUM DALAM MENINGKATKAN EFEKTIVITAS PROSES PEMBELAJARAN DI SEKOLAH - Lestari, Indah; Merjuki, Abdul Rahman; Susrianti, Ade; Melsanda, Dea; Negara, Malinda Atma; Yuniati, Yuniati; Andriesgo, Johan (Jurnal Manajemen Pendidikan, 2025)
Curriculum administration also plays a role in improving teacher professionalism. With structured management, teachers can more easily understand their duties and responsibilities, and receive support in the form of training, supervision, and periodic evaluation. This study aims to examine the role of curriculum administration in improving the effectiveness of the learning process in schools. Curriculum administration has a strategic function in designing, organizing, implementing, and evaluating learning activities so that they run in accordance with educational goals. Through a descriptive qualitative approach, data were collected through observation, interviews, and documentation in the school environment. The results of the study indicate that well-organized curriculum administration can improve the quality of learning planning, integration between subjects, and clarity of teacher task division. In addition, the support of curriculum administration in monitoring and evaluating learning contributes directly to improving teacher performance and student learning outcomes. Thus, curriculum administration has an important role as the main support in creating an effective and sustainable learning process.